3D organoid-derived human glomeruli for personalised podocyte disease modelling and drug screening. Issue 1 (December 2018) - Hale, Lorna; Howden, Sara; Phipson, Belinda; Lonsdale, Andrew; Er, Pei; Ghobrial, Irene; Hosawi, Salman; Wilson, Sean; Lawlor, Kynan; Khan, Shahnaz; Oshlack, Alicia; Quinlan, Catherine; et al.
Abstract The podocytes within the glomeruli of the kidney maintain the filtration barrier by forming interdigitating foot processes with intervening slit diaphragms, disruption in which results in proteinuria. Studies into human podocytopathies to date have employed primary or immortalised podocyte cell lines cultured in 2D. Here we compare 3D human glomeruli sieved from induced pluripotent stem cell-derived kidney organoids with conditionally immortalised human podocyte cell lines, revealing improved podocyte-specific gene expression, maintenance in vitro of polarised protein localisation and an improved glomerular basement membrane matrisome compared to 2D cultures. Organoid-derived glomeruli retain marker expression in culture for 96 h, proving amenable to toxicity screening. In addition, 3D organoid glomeruli from a congenital nephrotic syndrome patient with compound heterozygousNPHS1 mutations reveal reduced protein levels of both NEPHRIN and PODOCIN. Hence, human iPSC-derived organoid glomeruli represent an accessible approach to the in vitro modelling of human podocytopathies and screening for podocyte toxicity. Studies examining human podocytopathies have utilised 2D cultured primary or immortalised podocyte cell lines. Here, the authors demonstrate that 3D human glomeruli sieved from induced pluripotent stem cell-derived kidney organoids retain an improved podocyte identity in vitro facilitating disease modelling and toxicity testing.